Comparison of Chemical Composition in Decoctions of Aconitum kusnezoffii Reichb and Pinelliae rhizoma Praeparatum Extracted by Different Methods - Zhai, X.Y.; Xu, G.L.; Zhang, L.; Jin, C.; Feng, Y.L.; Li, B.T.; Yang, S.L. (Asian Journal of Chemistry, 2014)
To find the discrimination of the combination of Aconitum kusnezoffii reichb and Pinelliae rhizoma praeparatum from the chemical composition, two co-decoctions and two mixed decoctions were extracted by alcohol and water, respectively. Batches of these decoctions were analyzed by UHPLC/Q-TOF-MS. The datasets were analyzed by OSC-PLS-DA. The content of monoester-diterpenoid alkaloids (MDAs) including benzoylaconine (BAC), benzoylmesconitine (BMA), benzoylhypaconine (BHA) in MDW was lower than that in CDW, but the content of amine alkaloids (AAs) that including aconine, mesaconine, hypaconine in MDW was higher than that in CDW. The content of diester-diterpenoid alkaloids (DDAs) including aconitine (AC), mesaconitine (MA) and hypaconitine (HA) in MDA was lower than that in CDA, but 14-benzoyl-8-O-methyl-aconine, mesaconine, BMA, BHA, neojiangyouaconitine in MDA was lower than that in CDA. In both alcohol extraction and water extraction, the chemical composition of toxicity in mixing decoction was lower than that in co-decoction.